The quality analysis of polycrystalline diamond coated si3n4 using raman spectra: the effect of chamber pressure and microwave power - Purniawan, A. (2007)
Polycrystalline Diamond (PCD) is diamond grit that has been fused together under high-pressure, high-temperature conditions in the presence of a catalytic metal. The extreme hardness, wear resistance, and thermal conductivity of diamond make it an ideal material for bearings.